2015
DOI: 10.1080/07481187.2014.946625
|View full text |Cite
|
Sign up to set email alerts
|

From a Cracking Façade to a Total Escape: Maladaptive Perfectionism and Suicide

Abstract: This study explored the final stages of the suicide process among six men characterized as maladaptive perfectionists. These men, aged 22 to 58, had no history of suicide attempts or mental health treatment. In-depth interviews with 5 to 9 informants for each person were analyzed by using interpretative phenomenological analysis. Three themes emerged from the analysis: (a) a cracking façade; (b) a total loss of coping ability; and (c) a total escape. Suicide was related to a shameful defeat that was not revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Suicide. Some researchers in the field of suicidality agree that suicide is a multi-factorial process, and it generally understood that negative cognitions are a precursor to suicide (Kiamnesh et al, 2015). What is less understood in the interplay between perfectionism and suicidal ideation (Shahnaz et al, 2018;Smith et al, 2018).…”
Section: Psychological Consequences Of Perfectionismmentioning
confidence: 99%
“…Suicide. Some researchers in the field of suicidality agree that suicide is a multi-factorial process, and it generally understood that negative cognitions are a precursor to suicide (Kiamnesh et al, 2015). What is less understood in the interplay between perfectionism and suicidal ideation (Shahnaz et al, 2018;Smith et al, 2018).…”
Section: Psychological Consequences Of Perfectionismmentioning
confidence: 99%
“… 1 , 2 Suddarth and Slaney 4 conducted a factor analysis using three measures of perfectionism, The Hewitt and Flett Multidimensional Perfectionism Scale (HMPS), The Frost Multidimensional Perfectionism Scale (FMPS) and the Revised Almost Perfect Scale (APS-R) and found three factors which they labelled ‘maladaptive perfectionism’, ‘adaptive perfectionism’ and ‘orderliness’. A number of studies demonstrated that maladaptive perfectionism dimensions are strongly associated with negative outcomes, such as anxiety, depression and suicidal ideation, 5 , 6 whereas adaptive perfectionism dimensions have shown positive relationships with positive outcomes such as positive affect (PA), academic achievement and life satisfaction. 7 , 8…”
Section: Introductionmentioning
confidence: 99%
“…Entrapment is the perception that the defeat-generating situation cannot be resolved nor escaped (Gilbert & Allan, 1998). Some individuals see a form of liberation from entrapment through death, and the theme of escape is common in suicide (Baumeister, 1990;Ikunaga, Nath, & Skinner, 2013;Kiamanesh, Dieserud, & Haavind, 2015;Kovacs, Beck, & Weissman, 1975;Meyer, Irani, Hermes, & Yung, 2017). 2010) mediated the relationship between insomnia and suicidal ideation in university students.…”
Section: Young Adultsmentioning
confidence: 99%